2001
DOI: 10.1099/0022-1317-82-11-2805
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence analysis of a novel circovirus of canaries and its relationship to other members of the genus Circovirus of the family Circoviridae

Abstract: The circular, single-stranded DNA genome of a novel circovirus of canaries, tentatively named canary circovirus (CaCV), was cloned and sequenced. Sequence analysis indicated that the genome was 1952 nucleotides (nt) in size and had the potential to encode three viral proteins, including the putative capsid and replicationassociated (Rep) proteins. The CaCV genome shared greatest sequence similarity (58n3% nt identity) with the newly characterized columbid circovirus (CoCV) and was more distantly related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 14 publications
2
68
0
3
Order By: Relevance
“…This is the first reported use of the CAN-1F/CAN-IR primer pair, and the success achieved suggests that these primers may be useful for detecting other avian circoviruses that are more closely related to BFDV, PiCV and CaCV. The second PCR step, involving the use of inverse primers to amplify complete circular genomes as linear fragments, has been previously reported (Todd et al ., 2001). The accumulation of sequence data from an increasing range of avian circoviruses will not only be of value in the diagnosis by PCR of particular circovirus species or groups of closely related species, but, using a degenerate primer PCR approach, may also be valuable in detecting as yet undiscovered novel circoviruses that may be infecting farmed species such as chickens and turkeys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first reported use of the CAN-1F/CAN-IR primer pair, and the success achieved suggests that these primers may be useful for detecting other avian circoviruses that are more closely related to BFDV, PiCV and CaCV. The second PCR step, involving the use of inverse primers to amplify complete circular genomes as linear fragments, has been previously reported (Todd et al ., 2001). The accumulation of sequence data from an increasing range of avian circoviruses will not only be of value in the diagnosis by PCR of particular circovirus species or groups of closely related species, but, using a degenerate primer PCR approach, may also be valuable in detecting as yet undiscovered novel circoviruses that may be infecting farmed species such as chickens and turkeys.…”
Section: Discussionmentioning
confidence: 99%
“…The first PCR step capitalized on the probability that nucleotide sequences present in the CaCV genome, which were highly conserved when isolates of PiCV, BFDV and CaCV were compared, would also occur in the genomes of circoviruses that infect finches and gulls and that, as such, PCR amplification of circovirus amplicons would be facilitated. Earlier investigations used degenerate primers, selected after comparison of the PCV1 and BFDV genome sequences, to amplify small regions of the Rep genes of PiCV, GoCV and CaCV (Phenix et al ., 2001;Todd et al ., 2001b;Hattermann et al ., 2003). This is the first reported use of the CAN-1F/CAN-IR primer pair, and the success achieved suggests that these primers may be useful for detecting other avian circoviruses that are more closely related to BFDV, PiCV and CaCV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viruses from the genus Cyclovirus have been found in humans and chimpanzees 2. Circoviruses have a wide host range, including human,2, 3 birds,4, 5 pigs,6, 7 dogs,8 and cattle 9, 10. Before to 2015, porcine circovirus 1 (PCV1) and PCV2 were considered the only types of porcine circoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…In this species, circovirus-like particles have been detected by electron microscopy in negatively stained organ homogenates from dead birds from aviaries with a history of high mortality (Goldsmith, 1995;Guercio et al ., 2000) and identified as circoviruses using a polymerase chain reaction (PCR) assay . Nucleotide sequence analysis showed that this virus was a novel member of the Circovirus genus with greater sequence similarity with columbid circovirus than with psittacine beak and feather disease virus and porcine circoviruses types 1 and 2 (Phenix et al ., 2001).…”
Section: Introductionmentioning
confidence: 99%